Inflation and the Black Market Exchange Rate in a Repressed Market : A Model of Venezuela - Cerra, Valerie (IMF Working Papers; Working Paper ;, 2016)
This paper presents a stylized general equilibrium model of the Venezuelan economy. The model explains how the recent sharp fall in oil revenue combines with foreign exchange rationing to produce a steep rise in inflation. Counterintuitively, a devaluation of the official exchange rate could temporarily reduce inflation. The model also explains how the hyper-depreciation of the black market exchange rate reflects prices in the most distorted goods markets.